Impact of Oxidative Stress on Jordanian Children with Autism Spectrum Disorder - Al-Ramahi, Amal; Zakaraya, Zainab; AlTamimi, Lina; Hailat, Mohammad; Hamad, Mohammed F; Abu Dayyih, Wael; Alabbadi, Ibrahim; AlRaoush, Yousef; Al-Omari, Laila; Ahmed, Khaled Abdul-Aziz; Alhusban, Ala A (Jordan Journal of Pharmaceutical Sciences, 2025)
Background: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder whose etiology is still unknown and without clinical biomarkers. Recent studies have highlighted the potential role of oxidative stress and metabolic changes in ASD. However, little is known about these changes in the Jordanian ASD population. Aims: This study aimed to evaluate oxidative stress biomarkers in Jordanian children with ASD and to investigate the potential correlations with the disorder's clinical features. Methodology: This cross-sectional study involved 80 Jordanian children divided into two groups: the patients’ group (diagnosed with ASD, n=40) and the control group (healthy, n=40). The study examined the distribution of ASD among the participants and assessed the prevalence of comorbid conditions. It also evaluated oxidative stress biomarkers, including Glutathione Peroxidase (GPX), Superoxide Dismutase (SOD), and Malondialdehyde (MDA). Results: ASD was more common in males (65% in the ASD group) and in people with a family history of the disorder (55%). Common comorbid conditions included ADHD (42.5%), anxiety (25%), and epilepsy (15%). Children with ASD had significantly lower levels of GPX (2.72 ± 0.9 pmol/mL vs. 7.74 ± 2.5 pmol/mL in controls, p<0.005) and SOD (1.74 ± 0.75 ng/mL vs. 2.93 ± 0.98 ng/mL in controls, p<0.005) and higher levels of MDA (16 ± 1.95 nmol/mL vs. 5.46 ± 1.57 nmol/mL in controls, p<0.005). Conclusion: This study suggests a potential association between ASD and oxidative stress. While further research is required, these findings contribute to our understanding of ASD pathogenesis and may guide future diagnostic and therapeutic approaches. Pearson correlation coefficients imply that increased oxidative stress, as measured by lower GPX and SOD levels and higher MDA levels, may be linked to the severity and presence of clinical features in ASD.